2017
DOI: 10.1160/th17-03-0174
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase 2 is dispensable for platelet function

Abstract: Summary Increased intracellular reactive oxygen species (ROS) promote platelet activation. The sources of platelet-derived ROS are diverse and whether or not mitochondrial derived ROS, modulates platelet function is incompletely understood. Studies of platelets from patients with sickle cell disease, and diabetes suggest a correlation between mitochondrial ROS and platelet dysfunction. Therefore, we generated mice with a platelet specific knockout of superoxide dismutase 2 (SOD2-KO) to determine if increased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…Overall, our findings are consistent with prior studies demonstrating a role for ROS in platelet function 5,8,43,44 and further suggest that multiple oxidative pathways are involved in regulating platelet aggregation and thrombi formation. These observations are also in concordance with recent reports implicating mitochondrial ROS in platelet activation in certain disease states.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our findings are consistent with prior studies demonstrating a role for ROS in platelet function 5,8,43,44 and further suggest that multiple oxidative pathways are involved in regulating platelet aggregation and thrombi formation. These observations are also in concordance with recent reports implicating mitochondrial ROS in platelet activation in certain disease states.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Fidler and coworkers demonstrated that SOD2-KO platelets showed increased mitochondrial ROS; however, total platelet ROS content remained unchanged. Furthermore, deletion of SOD2 did not alter tail-bleeding or arterial thrombosis in vivo, suggesting that SOD2 is dispensable for platelet redox balance [ 81 , 82 ].…”
Section: Endogenous and Exogenous Antioxidant Systems As Regulatormentioning
confidence: 99%
“…Blood was isolated into 1:20 acid citrate dextrose through carotid artery cannulation as previously described (8). For GLUT1 protein analysis and Seahorse analysis, platelets were negatively depleted of leukocytes and red blood cells by incubation with CD45 and Terr119 microbeads (Milteny Biotec, Cambridge, MA).…”
Section: Platelet Isolationsmentioning
confidence: 99%